Patterning Techniques in Coplanar Micro/Nano Capacitive Sensors - Joo, Seokwon; Han, Jung Yeon; Seo, Soonmin; Kim, Ju Hyung (Micromachines, 2023)
Rapid technological advancements have led to increased demands for sensors. Hence, high performance suitable for next-generation technology is required. As sensing technology has numerous applications, various materials and patterning methods are used for sensor fabrication. This affects the characteristics and performance of sensors, and research centered specifically on these patterns is necessary for high integration and high performance of these devices. In this paper, we review the patterning techniques used in recently reported sensors, specifically the most widely used capacitive sensors, and their impact on sensor performance. Moreover, we introduce a method for increasing sensor performance through three-dimensional (3D) structures.
Keywords: 3D sensor; Coplanar-type capacitive sensor; Ink-jet printing; Laser patterning; Parallel plates; Parallel-plate capacitive sensor; Patterning techniques; Performance; Sensor performance; Soft-lithography; 3D sensors; coplanar-type capacitive sensors; inkjet printing; laser patterning; parallel-plate capacitive sensors; patterning techniques; screen printing; soft lithography